MENUMBUHKAN DISIPLIN POSITIF MELALUI PROSEDUR KELAS PADA MATA PELAJARAN BAHASA INGGRIS DI KELAS VII - Novita Aryuntini (Dinas Pendidikan dan Kebudayaan Kabupaten Kubu Raya Provinsi Kalimantan Barat, 2025)
This study aims to enhance the positive discipline of seventh-grade students through the implementation of classroom procedures in English language instruction at SMP Negeri 6 Teluk Pakedai. The research was prompted by the observed absence of clearly developed positive disciplinary character and behavior among students. A qualitative approach was selected as the most appropriate methodology for this study. Data collection was carried out through observation and surveys, using observation sheets and questionnaires as instruments. The classroom procedures were developed with student involvement and implemented consistently over a period of several months. The results of the study indicate a significant improvement in various aspects of student discipline, including orderliness, punctuality, obedience, self-control, responsibility, and consistency. This was evidenced by observation and survey results, which demonstrated an increase in the percentage of students exhibiting positive disciplinary behavior, rising from 16 percent to 66 percent following the implementation of classroom procedures over several months. The most notable improvements were observed in orderliness, punctuality, and responsibility. These findings are consistent with previous research indicating that the application of clear and consistent classroom procedures can be effective in shaping student discipline. In conclusion, the implementation of classroom procedures represents an effective strategy for fostering positive discipline among students.